(untitled) (REMUNOM, 2025)
Creatine, an amino acid naturally present in the body and in foods, is widely recognized as an outstanding ergogenic resource in sports and physical activities. This study aimed to investigate the relationship between the use of creatine as a nutritional supplement and improved performance in physical activities in the literature. To this end, a bibliographic survey was conducted on platforms such as PubMed, SciELO, LILACS and Google Scholar, using the descriptors "Creatine", "nutritional supplement" and "physical performance". The review included articles that address everything from the mechanisms of action of creatine, its role in energy metabolism and cellular protection, to the effectiveness of different supplementation protocols. The findings in the literature corroborate that creatine increases the availability of muscle phosphocreatine, which is essential for ATP resynthesis and, consequently, for improving performance in high-intensity, short-duration exercises. Creatine supplementation is an effective and safe means when properly guided, contributing to physical and sports development. The need for professional monitoring, especially from a nutritionist, is highlighted for adequate prescription, monitoring and risk prevention, ensuring the conscious and personalized use of this resource.